2014
DOI: 10.17138/tgft(2)271-277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of season on the quality of forages selected by sheep in citrus plantations in Ghana

Abstract: The study aimed at assessing the effects of season on chemical composition of forages selected by sheep grazing in a citrus plantation. Forage species growing in a sweet orange (Citrus sinensis) plantation were identified and sampled monthly for 2 years. Samples were bulked on monthly basis for chemical analysis. The average dry matter content of the forages increased from the rainy to the dry season but effects of season on the chemical components were inconsistent. Some species, such as Asystasia gangetica, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Mineral (mg l -1 , n = 3 www.nature.com/scientificreports/ Nitrogen content in plants did not change between seasons which may be because the plant cells in dry season contained higher water content than wet season which affected the total N or crude protein 43 . Therefore, the N of banteng dung in the breeding cage and natural habitat in both dry and wet seasons was not different.…”
Section: Discussionmentioning
confidence: 98%
“…Mineral (mg l -1 , n = 3 www.nature.com/scientificreports/ Nitrogen content in plants did not change between seasons which may be because the plant cells in dry season contained higher water content than wet season which affected the total N or crude protein 43 . Therefore, the N of banteng dung in the breeding cage and natural habitat in both dry and wet seasons was not different.…”
Section: Discussionmentioning
confidence: 98%
“…The values of hemicellulose reported in the study were far lower than the values reported in eastern Ethiopia (Derero and Kitaw, 2018) probably due to the season and harvesting stage. Various studies indicated that the chemical composition of the fodder trees varied with the phonological stage (Balehegn and Hintsa, 2015) and harvesting season (Abebe et al, 2012;Adjorlolo et al, 2014;Yayneshet et al, 2009). The NDF and ADF values reported for Acacia abyssinica and Erythrina abyssyinica in the study were lower and higher, respectively, than the values found in western Ethiopia (Yisehak and Janssens, 2013), unlike their ADL values.…”
Section: Nutritional Value Parametersmentioning
confidence: 52%
“…The values of the hemicellulose reported in the study were far lower than the values reported in eastern Ethiopia (Derero and Kitaw, 2018) probably due to the season and harvesting stage. Various studies indicated that the chemical composition of the fodder trees varied with the phonological stage (Balehegn and Hintsa, 2015) and harvesting season (Abebe et al, 2012;Adjorlolo et al, 2014;Yayneshet et al, 2009). The NDF and ADF values reported for Acaccia abyssinica and Erythrina abyssyinica in the study were lower and higher respectively than the values found in western Ethiopia (Yisehak and Janssens, 2013), unlike their ADL values.…”
Section: The Nutritional Value Parametersmentioning
confidence: 53%